The Honolulu index of plastic surgery 1971 A.D. to 1976 A.D. (The McDowell indexes of plastic surgical literature, 1977)
Comprehensive index to world literature of plastic surgical literature from text and abstracts of journal Plastic and reconstructive surgery, as well as from other sources. Index medicus format with authors and subjects interfiled. Entry gives bibliographical information for abstract location in Plastic and reconstructive surgery and also for original source.